INTEGRASI VERTIKAL DAN EFISIENSI INDUSTRI: INDUSTRI KERTAS TAHUN 1979-1997 DENGAN PENDEKATAN ERROR CORRECTION MODEL - Karseno, Arief Ramelan; Mulyaningsih, Tri (Journal of Indonesian Economy and Business, 2002)
The purpose of this paper is to measure the relationship between vertical integration ratio with three explanation variables: demand growth, concentration industry and cost of input. The result of the study give us information about factors that influence vertical integration so the company and government can take the best policy to increase efficiency.The case study are pulp and paper industry from 1979 up to 1997. The use of such Error Correction Model (ECM) constitutes an effective framework for establishing links between the short and long-run approaches to econometric modeling. The empirical result show that vertical integration is an important step for company to protect their raw material supply and reduce price inefficiency.Keywords: vertical integration is an important step to increase efficiency.